Pengaruh Biaya Operasional, Pendapatan dan Intensitas Research and Development terhadap Kinerja Keuangan pada Perusahaan Subsektor Farmasi yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Intan Nuraulia Hajari; Djuwita, Diana; Nakhwatunnisa, Haulah (Fakultas Ekonomika dan Bisnis Universitas PGRI Kanjuruhan Malang, 2025)
This study aims to analyze the effect of operating costs, revenue, and Research and Development (R&D) intensity on financial performance in pharmaceutical subsector companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. Financial performance in this study is measured using Return on Assets (ROA). This research uses quantitative methods with panel data regression models. The population in this study were pharmaceutical companies listed on the IDX, with samples selected using purposive sampling method, so that 7 companies were obtained with a total of 35 observation data. The results showed that partially, operating costs have a negative and significant effect on ROA, while revenue has a positive and significant effect on ROA. Meanwhile, R&D intensity has no significant effect on ROA, which indicates that investment in research and development has not had a direct impact on the profitability of pharmaceutical companies in the period studied. However, simultaneously, the three variables have a significant effect on the company's financial performance. Keywords: Operating expenses; Revenue; R&D Intensity; Financial Performance; ROA.